Răspuns :
6x/5-x=x/3+8
se aduce la acelasi numitor comun, in acest caz este 15
se amplifica primul termen cu 3, al doilea cu 15, al treilea cu 5 si ultimul cu 15
6x·3-x·15=x·5+8·15
18x-15x=5x+120
3x-5x=120
-2x=120
x=-60
se aduce la acelasi numitor comun, in acest caz este 15
se amplifica primul termen cu 3, al doilea cu 15, al treilea cu 5 si ultimul cu 15
6x·3-x·15=x·5+8·15
18x-15x=5x+120
3x-5x=120
-2x=120
x=-60
[tex] \frac{6x}{5} -x= \frac{x}{3} +8 \\
\frac{6x-5x}{5} = \frac{x+24}{3} \\
\frac{x}{5} = \frac{x+24}{3} \\
3x=5x+120=\ \textgreater \ -2x=120=\ \textgreater \ x=-60[/tex]